Teachers Perspectives of ICT Integration in English Language Teaching: A Review of Literature - Hafifah, Gusti Nur (Universitas Muhammadiyah Sidoarjo, 2020)
This paper reviews some research articles on the teachers perspective of ICT implementation in education, particularly in English language teaching. It explores the research result based on three scopes; Teachers perspective of ICT in education in general, Teachers perspective of ICT specifically in English language Teaching in Global Context, and The teachers perspectives of ICT in ELT in Indonesian settings. The analysis is based on the research methodology; including the design, subject and instrument used in the research, also the findings and suggestions resulted in the research. Finally, this paper proposes further study on the related topic area on teachers’ cognition of ICT in ELT. HIGHLIGHTS: Teachers have positive perspectives on the use of ICT for education and ELT. There are limited studies on teachers perspectives in higher education level. Teachers perspective on ICT might be contributing factors to teachers professional development.